Correlation of Federal Test Method Standard 791B Method 354 with Army 240-Hour Tracked Vehicle Test Cycle Method 355T. - Montemayor,A F; Frame,E A; Owens,E C (1983)
Currently the U.S. Army has two full-scale engine tests which are used for qualifying engine oils. Both tests are based on the Detroit Diesel 6V-53T engine with a number of similarities between the two test procedures. The first of these tests is Method 354, FTMS 791B for qualification of MIL-L-46167 arctic engine oils (OEA) while the other is the newly released Method 355T, FTMS 791B for qualification of MIL-L-2104D tactical engine oils (OE/HDO). One of the main differences between these two test procedures is that the Method 354 procedure uses an aluminum engine block which is no longer available from the manufacturer. Other differences are that this method is run for a shorter test duration at a lower engine power output level under steady-state conditions. The unavailability of the cast aluminum cylinder block from the manufacturer and the phase-out of this aluminum engine from the Military inventory means that Method 354 must be updated or replaced. This project was an attempt to develop a correlation between the two test methods by comparing results from Method 355T with results from Method 354 using the lubricants used in developing and standardizing Method 354.